Retratos de famílias: trajetórias patrimoniais - Bieger, Tamires Elisa (2017)
The objective of the research was to understand the trajectory of patrimonial transmission of family farmers, based on the experiences lived by three generations. The central question posed to the research was: What are the strategies associated with the patrimonial transmission and the social transformations built and established over the time of the family farmers? The case study was carried out in the municipality of Coronel Barros, located in the northwestern part of the state of Rio Grande do Sul, whose criteria were the representativeness of family farmers and the prior knowledge of the families with generations of grandparents, parents and children. From a qualitative approach, in a first moment was collected secondary data, through the bibliographical and documentary research, in the second moment, primary data was collected through the techniques of semi-structured interview and observation. The use of heritage trajectories have the purpose to make a retrospect of the individual and family experiences, in investment to understand whether current choices are influenced by past experiences, in view of family farmers ability to choose the guiding principles of their choices, that is, habitus, and how to re-elaborate it, reinterpret it, reconstruct it with reference to the different social and economic realities. The trajectories run through different points of discussion, based on intergenerational relations, which are linked to realities known or lived within families and reproduced based on positive or negative references acquired in the lived paths. The strategies that are established in the family group and the conjunctures given by experiences in migration, work, marriage, gender relations, schooling and heritage formation, but which acquire new meanings, according to socioeconomic and family changes. Experienced as a process, the family trajectories of transmission, heritage and division of land are socially constructed with references to a set of social, economic, legal and cultural relations that give meaning to the changes in the relations to the heritage trajectories of the family farmers of Coronel Barros.